2020
DOI: 10.3390/ijerph17165700
|View full text |Cite
|
Sign up to set email alerts
|

First-Year Antibiotics Exposure in Relation to Childhood Asthma, Allergies, and Airway Illnesses

Abstract: Background: Associations of early antibiotics exposures with childhood asthma, allergies, and airway illnesses are debated. Objectives: We aimed to investigate associations of first-year antibiotics exposure with childhood asthma, allergies, and airway illnesses. Methods: A cross-sectional study was conducted among preschoolers in Shanghai, China during 2011–2012. A questionnaire regarding household environment and lifestyles and childhood health outcomes was reported by the child’s parents. Results: In total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…Besides, we also found that antibiotic use during childhood played a leading role in susceptibility to allergic diseases, consistent with the observations of most previous studies (20,21). This finding is biologically plausible.…”
Section: Discussionsupporting
confidence: 92%
“…Besides, we also found that antibiotic use during childhood played a leading role in susceptibility to allergic diseases, consistent with the observations of most previous studies (20,21). This finding is biologically plausible.…”
Section: Discussionsupporting
confidence: 92%
“…Forty studies in 1,602,639 children (183,244 cases with one study not reporting number of cases) investigated the association between antibiotic exposure and the risk of developing atopic dermatitis, evaluated by the International Study of Allergy and Asthma in Childhood (ISAAC) questionnaire, international classification of disease (ICD) codes, parent-reported symptoms or physician's diagnosis, the Criteria by the American Academy of Dermatology, Hanifin and Rajka criteria or William's criteria (table 1). 32,37,40,43,[48][49][50][51]53,62,79,80,82,93,96,98,103,105,114,120,123,129,135,150,[153][154][155]157,161,162,[172][173][174][175][176][177][178][179][180][181] Of the 40 studies, 38 (95%) investigated the effect of antibiotic exposure in the first five years of life (36 (90%) in the first two years of life). 32,…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…32,37,40,43,[48][49][50][51]53,62,79,80,82,93,96,98,103,105,114,120,123,129,135,150,[153][154][155]157,161,162,[172][173][174][175][176][177][178][179][180][181] Of the 40 studies, 38 (95%) investigated the effect of antibiotic exposure in the first five years of life (36 (90%) in the first two years of life). 32,37,40,43,[48][49][50][51]53,62,79,…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…A case-control study of Kawasaki disease (KD), including 50 patients and 200 control subjects, showed that the development of KD was associated with previous antibiotic administration and that antibiotics might contribute to the development of KD by affecting the intestinal microbiota in infants and young children ( 149 ). Additionally, long-term antibiotic exposure has been associated with an increased risk for several diseases, such as type 2 diabetes ( 150 ), inflammatory bowel diseases ( 151 ), and asthma ( 152 ). Therefore, the interaction of antibiotics and intestinal microbiota must be taken into account when administrating antibiotics.…”
Section: Commonly Used Methods To Regulate the Microbiotamentioning
confidence: 99%